Moxibution sebagai Alternatif Penanganan Letak Sungsang - Waslia, Dede (Faculty of Health Science and Technology, University of Jenderal Achmad Yani, 2021)
Breech pregnancy affects in the complications of childbirth that cause maternal death, where 3-4% of childbirth in Indonesia consists of breech position. Head birth in the breech location does not have a mechanism